Arsenic: Environmental Chemistry, Health Threats and Waste Treatment - Henke, Kevin R. (Wiley, 2012)
This book presents an overview of the chemistry, geology, toxicology and environmental impacts of arsenic, presenting information on relatively common arsenic minerals and their key properties. In addition, it includes discussions on the environmental impacts of the release of arsenic from mining and coal combustion.